2018
DOI: 10.1016/j.biosystemseng.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Development of passive flux samplers based on adsorption to estimate greenhouse gas emissions from agricultural sources

Abstract: Passive flux samplers (PFSs) packed with adsorbents are used to estimate gaseous emissions. A key condition of their use is maintaining a linear relationship between internal and external air velocities. The performance of PFSs designs depends on the characteristics of the adsorption bed and on the sampler design. The parameters required to enable PFSs to estimate greenhouse (GHG) emissions from agricultural sources were studied. The effect of the particle size of the adsorbent used as collector medium was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…During this study, the average wind speed was low at 1.4 m·s −1 and the maximum wind speed was always below 10 m·s −1 . Previous research has shown that at the same external wind speed, the pressure drop across an orifice plate decreases as the orifice diameter increases (Larios et al., 2018; Yin et al., 2021). Thus, at the same low wind speed in the field, a 1‐mm orifice would be expected to have greater turbulence than a 2‐mm orifice, which may have led to better contact with the tube wall, better NH 3 adsorption, and greater measurement of NH 3 volatilization loss.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…During this study, the average wind speed was low at 1.4 m·s −1 and the maximum wind speed was always below 10 m·s −1 . Previous research has shown that at the same external wind speed, the pressure drop across an orifice plate decreases as the orifice diameter increases (Larios et al., 2018; Yin et al., 2021). Thus, at the same low wind speed in the field, a 1‐mm orifice would be expected to have greater turbulence than a 2‐mm orifice, which may have led to better contact with the tube wall, better NH 3 adsorption, and greater measurement of NH 3 volatilization loss.…”
Section: Resultsmentioning
confidence: 98%
“…One of the methods that can measure actual NH 3 loss under field conditions is the integrated horizontal flux (IHF) that uses anemometers and dynamic air samplers placed at different heights from the soil surface. This method requires expensive and complex equipment as well as the availability of electrical power in the field, which makes it difficult to have many treatment replications (Larios et al., 2018). The development of IHF methods with passive instead of dynamic flux samplers has reduced costs and made replications more feasible under field conditions (Leuning et al., 1985; Schjoerring et al., 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the atmospheric levels of ammonia can vary greatly between locations world‐wide, [19] the ammonium content in the membrane will highly depend on the location of the experiment. The atmospheric concentration of ammonia also highly depends upon temperature and season (fertilizer application) [20] . Measurements of aerosol NH 3 in Heimaey, an active volcano island south of Iceland, demonstrated 0.05–0.12 ppb NH 3 in air [21] .…”
Section: Methods No Methods Name Container Procedure[b]mentioning
confidence: 99%
“…The atmospheric concentration of ammonia also highly depends upon temperature and season (fertilizer application). [20] Measurements of aerosol NH 3 in Heimaey, an active volcano island south of Iceland, demonstrated 0.05-0.12 ppb NH 3 in air. [21] Atmospheric concentrations have been measured in various cities worldwide and reported between 3 ppb and 100 ppb (up to 800 times the reported concentration in Heimaey) depending on location and time.…”
Section: Angewandte Chemiementioning
confidence: 99%